On a Graph-Based Semantics for UML Class and Object Diagrams - Rensink, Arend; Kleppe, Anneke (Electronic Communications of the EASST, 2008)
In this paper we propose a formal extension of type graphs with notions that are commonplace in the UML and have long proven their worth in that context: namely, inheritance, multiplicity, containment and the like. We believe the absence of a comprehensive and commonly agreed upon formalisation of these notions to be an important and, unfortunately, often ignored omission. Since our eventual aim (shared by many researchers) is to give unambiguous, formal semantics to the UML using the theory of graphs and graph transformation, in this paper we propose a set of definitions to repair this omission. With respect to previous work in this direction, our aim is to arrive at more comprehensive and at the same time simpler definitions.